Analysis of global gene expression changes in human bronchial epithelial cells exposed to spores of the allergenic fungus, Alternaria alternata - Babiceanu, Mihaela; Howard, Brad; Rumore, Amanda; Kita, Hirohito; Lawrence, Christopher (Frontiers in Microbiology, 2013)
Exposure and sensitivity to ubiquitous airborne fungi such as Alternaria alternata have long been implicated in the development, onset, and exacerbation of chronic allergic airway disorders. This present study is the first to investigate global changes in host gene expression during the interaction of cultured human bronchial epithelial cells and live Alternaria spores. In in vitro experiments human bronchial epithelial cells (BEAS-2B) were exposed to spores or media alone for 24 hours. RNA was collected from three biological replicates per treatment and was used to assess changes in gene expression patterns using Affymetrix Human Genome U133 Plus 2.0 Arrays. In cells treated with Alternaria spores compared to controls, 613 probe sets representing 460 individual genes were found differentially expressed (p<0.05). In this set of 460 statistically significant, differentially expressed genes, 397 genes were found to be up-regulated and 63 were down-regulated. Of these 397 up-regulated genes, 156 genes were found to be up-regulated >2 fold. Interestingly, none of the 63 down-regulated genes were found differentially expressed at <-2 fold. Differentially expressed genes were identified following statistical analysis and subsequently used for pathway and network evaluation. Interestingly, many cytokine and chemokine immune response genes were up-regulated with a particular emphasis on interferon-inducible genes. Genes involved in cell death, retinoic acid signaling, and TLR3 response pathways were also significantly up-regulated. Many of the differentially up-regulated genes have been shown in other systems to be associated with innate immunity, inflammation and/or allergic airway diseases. This study now provides substantial information for further investigating specific genes and innate immune system pathways activated by Alternaria in the context of allergic airway diseases.